What is the solution of the equation  x/3−9=6  solving for

  1. Solving Linear Equations Unit Test Solve for x to determine if the equation has one, none, or infinite solutions 11x = 3(7x - 1)
    1. answers icon 1 answer
    2. views icon 75 views
  2. Look at the steps for solving the equation and choose a true statement.3x−9x+1=2(−3x+1)−1 −6x+1=−6x+2−1
    1. answers icon 1 answer
    2. views icon 67 views
  3. 2. Look at the steps for solving the equation and choose a true statement.3x−9x+1=2(−3x+1)−1 −6x+1=−6x+2−1
    1. answers icon 1 answer
    2. views icon 337 views
  4. 2. Look at the steps for solving the equation and choose a true statement.3x−9x+1=2(−3x+1)−1 −6x+1=−6x+2−1
    1. answers icon 1 answer
    2. Memes Goofy ahh ohio asked by Memes Goofy ahh ohio
    3. views icon 278 views
  5. Look at the steps for solving the equation and choose a true statement.3x−9x+1=2(−3x+1)−1 −6x+1=−6x+2−1
    1. answers icon 1 answer
    2. Dez asked by Dez
    3. views icon 225 views
  6. Look at the steps for solving the equation and choose a true statement.3x−9x+1=2(−3x+1)−1 −6x+1=−6x+2−1
    1. answers icon 1 answer
    2. Ihateconnexus asked by Ihateconnexus
    3. views icon 237 views
  7. While solving an equation, if the variable term becomes zero, and the equation makes a true statement, then the solution is one
    1. answers icon 1 answer
    2. Addi_Joy9172 asked by Addi_Joy9172
    3. views icon 152 views
  8. While solving an equation, if the variable term becomes zero, and the equation makes a true statement, then the solution is. no
    1. answers icon 1 answer
    2. views icon 11 views
  9. 2. Look at the steps for solving the equation and choose a true statement.3x−9x+1=2(−3x+1)−1 −6x+1=−6x+2−1
    1. answers icon 1 answer
    2. views icon 16 views
  10. Look at the steps for solving the equation and choose a true statement.3x−9x+1=2(−3x+1)−1 There are no solutions to the
    1. answers icon 3 answers
    2. views icon 47 views